Acupuncture and related interventions for smoking cessation. - White, A; Rampes, H; Liu, J; Stead, L; Campbell, J (2011)
BACKGROUND: Acupuncture and related techniques are promoted as a treatment for smoking cessation in the belief that they may reduce nicotine withdrawal symptoms. OBJECTIVES: The objectives of this review are to determine the effectiveness of acupuncture and the related interventions of acupressure, laser therapy and electrostimulation in smoking cessation, in comparison with no intervention, sham treatment, or other interventions. SEARCH STRATEGY: We searched the Cochrane Tobacco Addiction Group specialized register, the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE, BIOSIS Previews, PsycINFO, Science Citation Index, AMED, Acubriefs in November 2010; and four Chinese databases: Chinese Biomedical Database, China National Knowledge Infrastructure, Wanfang Data and VIP in November 2010. SELECTION CRITERIA: Randomized trials comparing a form of acupuncture, acupressure, laser therapy or electrostimulation with either no intervention, sham treatment or another intervention for smoking cessation. DATA COLLECTION AND ANALYSIS: We extracted data in duplicate on the type of smokers recruited, the nature of the intervention and control procedures, the outcome measures, method of randomization, and completeness of follow up.We assessed abstinence from smoking at the earliest time-point (before six weeks), and at the last measurement point between six months and one year. We used the most rigorous definition of abstinence for each trial, and biochemically validated rates if available. Those lost to follow up were counted as continuing smokers. Where appropriate, we performed meta-analysis using a fixed-effect model. MAIN RESULTS: We included 33 reports of studies. Compared with sham acupuncture, the fixed-effect risk ratio (RR) for the short-term effect of acupuncture was 1.18 (95% confidence interval 1.03 to 1.34), and for the long-term effect was 1.05 (CI 0.82 to 1.35). The studies were not judged to be free from bias. Acupuncture was less effective than nicotine replacement therapy (NRT). There was no evidence that acupuncture is superior to waiting list, nor to psychological interventions in short- or long-term. The evidence on acupressure and laser stimulation was insufficient and could not be combined. The evidence suggested that electrostimulation is not superior to sham electrostimulation. AUTHORS' CONCLUSIONS: There is no consistent, bias-free evidence that acupuncture, acupressure, laser therapy or electrostimulation are effective for smoking cessation, but lack of evidence and methodological problems mean that no firm conclusions can be drawn. Further, well designed research into acupuncture, acupressure and laser stimulation is justified since these are popular interventions and safe when correctly applied, though these interventions alone are likely to be less effective than evidence-based interventions.